2011
DOI: 10.1016/j.bbmt.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Low Risk of Chronic Graft-versus-Host Disease and Relapse Associated with T Cell–Depleted Peripheral Blood Stem Cell Transplantation for Acute Myelogenous Leukemia in First Remission: Results of the Blood and Marrow Transplant Clinical Trials Network Protocol 0303

Abstract: Graft versus host disease (GVHD) is most effectively prevented by ex vivo T cell depletion (TCD) of the allograft but its role in the treatment of patients undergoing allogeneic hematopoietic cell transplantation (HCT) for acute myeloid leukemia (AML) in complete remission (CR) remains unclear. We therefore performed a Phase 2 single arm multi-center study to evaluate the role of TCD in AML patients in CR1 or CR2 up to the age of 65 years. The primary objective was to achieve a disease-free survival (DFS) rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 40 publications
9
104
0
1
Order By: Relevance
“…For instance, dose intensity appears to be more important for early-stage, good-risk AML in which GVL seems less necessary. 22 This was also recently demonstrated in a randomized study of reduced vs myeloablative conditioning for patients with acute myeloid leukemia or myelodysplastic syndrome, in which the relapse rate was unacceptably high in the reduced intensity arm, closing the trial down earlier than expected. 23 It may be even more complicated than just reduced vs myeloablative conditioning.…”
Section: Atg Could Be Compromising Graft-versus-tumor Activitymentioning
confidence: 76%
See 1 more Smart Citation
“…For instance, dose intensity appears to be more important for early-stage, good-risk AML in which GVL seems less necessary. 22 This was also recently demonstrated in a randomized study of reduced vs myeloablative conditioning for patients with acute myeloid leukemia or myelodysplastic syndrome, in which the relapse rate was unacceptably high in the reduced intensity arm, closing the trial down earlier than expected. 23 It may be even more complicated than just reduced vs myeloablative conditioning.…”
Section: Atg Could Be Compromising Graft-versus-tumor Activitymentioning
confidence: 76%
“…Another T-cell depletion approach that has effectively reduced GVHD rates is CD34 selection, which removes T cells from the graft before stem cell infusion into the patient. 22,30 This strategy again offers a reduction in acute and chronic GVHD, but does not improve survival because of the increased infectionrelated deaths. Although ATG has been compared with standard GVHD prophylaxis strategies that include a calcineurin inhibitor and methotrexate, it is unclear if ATG is a better prophylactic strategy in comparison with these other T-cell depletion strategies.…”
Section: Atg In the Landscape Of Other Gvhd Prophylactic Strategiesmentioning
confidence: 99%
“…Finally, we acknowledge that other approaches may decrease risk for chronic GvHD and promote immune tolerance. Ex vivo T-cell depletion and post-transplantation cyclophosphamide hold promise, 11,13 as do in vivo T-cell depletion strategies such as ATG. 12,46 Furthermore, the use of marrow versus peripheral blood is associated with less chronic GvHD.…”
Section: Discussionmentioning
confidence: 99%
“…5 This represents a major obstacle to the success of HCT, as chronic GvHD remains a major source of late HCT-associated morbidity and death, [7][8][9] and is associated with prolonged immune suppressive therapy. 10 In contrast, ex vivo and in vivo T-cell depletion strategies (including ATG and post-transplant cyclophosphamide) are associated with lower risk of chronic GvHD, [11][12][13] and merit ongoing study. The optimal type and duration of immune suppressive therapy to mitigate risk for serious chronic GvHD and effectively induce tolerance remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Two small phase-2 non-randomized studies reported grafts of CD34-positive cells decrease the likelihood of being diagnosed with chronic and possibly acute GvHD without increasing leukaemia relapse compared with historic controls. 13,14 Because most or all immune cells were removed from the graft post transplant, anti-leukaemia activity was either mediated by other mechanisms (such as cytokines) or by immune cells developing from the graft (or both). A retrospective, non-pre-specified analysis of a phase-2 study of umbilical cord blood cell transplants reported a lower leukaemia relapse risk without more diagnosed acute or chronic GvHD.…”
mentioning
confidence: 99%